VARIETIES OF METHODS IN CLT (COMMUNICATIVE LANGUAGE TEACHING), ITS PRACTICALITIES OF TEACHING - Tsakanyan, Anush (MMIT Proceedings, 2023)
Communication skill is one of the elements of generic skills that are essential among university students. Through their years at the university, students would have been exposed to situations, in and outside of the lecture halls, where they have to use their communication skills, for example group assignments and class presentations in various disciplines. Therefore, the aim of this paper is to present some features of CLT and different ways of practicalities that teachers may use among university students. This method may be used not only by language, literature, history and other humanitarian science teachers, but by “exact” science teachers as well. Based on the observation, this article shows that only in correlation within the characters like teaching environment.